The Forecasting of Corrosion Damage of Structural Materials during Dry Long-Term Storage of RD BN-350 SNF with CC-19 SFA - Ye. T. Koyanbayev; M. K. Skakov; E. G. Batyrbekov; I. I. Deryavko; Ye. Ye. Sapatayev; Ye. A. Kozhahmetov (Science and Technology of Nuclear Installations)
There are results of long-term thermal aging of samples of irradiated and nonirradiated FA jacket and nonirradiated fuel element cladding at a temperature range from 300 to 550°C in argon, to 600°C in air. Materials have been studied before and after thermal tests. The forecast estimation of expected corrosion damage of barrier material at the radionuclide release from spent fuel assemblies of BN-350 reactor into environment during dry storage for 50 years was carried out.